impact of advances of exchange rate on scale of trade volume between Sudan and Egypt (2000-2018) - اد. سعد عبد الله الكرم; د. أيمن عبد الغني حمزة; محمد عبد الله أبو الصن (White Nile Journal for Studies and Research, 2020)
The paper aims at studying the impact of advances of exchange rate on scale of trade volume hetween Sudan and Egypt (2000-2018) The paper aims to answer the question, what is the effect of exchange rate on the balance of between the two Countries?. The paper hypothesized that there is statistically significant relation between the exchange rate and the independent variables including(Exports to Egypt, Import from Egypt, and balance of trade). The paper has used the statistical and descriptive analysis approache to analyze the data. The paper found that there is a weakness in the trade volume movement between Sudan and Egypt, which medicate that market, managerial, and political problems that the growing of trade lean for the good of Egypt, therefore, the deficit of Sudanese balance of trade is due to the high prices of import bills and lower prices of export bills. When balance of trade decreases by one unit the exchange rate increases approximately by 27.71 units. When Import from Egypt increases by one unit the exchange rate increases approximately by 3.05 units. When export To Egypt increases by one unit the exchange rate decreases approximately about 18.11units. The paper recommended that the government should monitor that economic performance and to coordinate between the two countries especially in an intraregional trade, also setting up a free zone trader in order to increase the scale volume of trade, in addition to encouraging the private scale volume of trade. in addition to encouraging the pirate sector, local foreign investment, achieving economic partnership, activating the bilateral economic cooperation conventions, codes and standards, trade zone, customs, and facilitate trade between the two countries. Key Words trade volume, exchange rate